Evaluation of low-intensity laser photobiomodulation in the treatment of traumatic oral ulcer: na integrative literature review (Research, Society and Development, 2022)
Traumatic ulcers are one of the most common injuries in the dental clinic and are caused by several factors, such as: occlusion trauma, poorly adapted prostheses, orthodontic appliances, among others. The present study sought to evaluate the photobiomodulatory effect of low-level laser in the treatment of traumatic oral ulcers through a qualitative, exploratory and descriptive literature review. Data collection was carried out in the Scielo, PubMed and BVS databases, and the descriptors chosen for the search were: Oral Ulcers, Low-Intensity Light Therapy, Lasers, Healing and Mouth. Studies between 2011 and 2021 written in English or Portuguese, published in indexed or unindexed journals, with full availability were selected. The selection of the corresponding works judiciously followed the sequence of reading the titles, abstracts and full reading of the articles. In Excel software, tables were built with the studies included in this review, including data regarding the type of study, published journal, database, language, author, year of publication, study objective, treatments used, sample, study groups, euthanasia time and laser parameters. At the end of the search, 13 clinical trials were selected. Totaling 654 samples of clinical results and their studied articles. It is concluded that low-level laser therapy proved to be an alternative capable of inducing photobiomodulation of traumatic oral ulcers.